Detection of virulence genes and antimicrobial resistance profiles of Escherichia coli isolates from raw milk and artisanal cheese in Southern Brazil - Leandro Parussolo; Ricardo Antônio Pilegi Sfaciotte; Karine Andrezza Dalmina; Fernanda Danielle Melo; Ubirajara Maciel Costa; Sandra Maria Ferraz (Semina: Ciências Agrárias, 2019)
The serrano artisanal cheese is a typical product from South region of Brazil, which is produced by skilled cheesemakers using raw milk. The contamination of this food by Escherichia coli has a great impact on public health, since it could threat the consumers’ health. The study evaluated the presence of virulence genes, antimicrobial susceptibility profiles and bofilm-production ability of Escherichia coli isolates obtained from raw milk and artisanal cheese produced in Southern Brazil. A total of 117 isolates of E. coli were characterized by multiplex PCR to detect the following virulence genes: eae for enteropatogenic E. coli (EPEC), lt and st for enterotoxigenic E. coli (ETEC), stx for shiga toxin-producing E. coli (STEC), stx and eae for enterohemorrhagic E. coli (EHEC), ipaH for enteroinvasive E. coli (EIEC) and aggR for enteroaggregative E. coli (EAEC). In addition, antimicrobial susceptibility profile to 22 antimicrobial agents was also performed by disk diffusion method, and we searched for extended-spectrum beta-lactamases (ESBL) and/or carbapenemase- producing isolates. Isolates that were positive for ESBL and carbapenemase were further investigated for the presence of the genes: blaTEM, blaSHV, blaOXA, blaCTX-M, for ESBL and blaOXA-48 for carbapenemase. Further, isolates had their ability to form biofilms investigated by the red Congo agar method. Virulence genes of E. coli were identified in 21.37% of the tested isolates, which were classified as EPEC (the most prevalent pathotype) and ETEC or EAEC. Ten (8.55%) of the total studied E. coli isolates revealed a multidrug-resistant profile, since they were resistant to three or more antimicrobial classes; whereas four isolates (3.42%) were classified as ESBL-producers and showed the presence of blaTEM gene. None of the isolates exhibited carbapenemase activity nor did they carry carbapenemase genes. From the total of E. coli isolates, 79 (67.52%) were considered potential biofilm producers. These results address a serious public health issue, since artisanal cheeses pose a risk to consumers’ health, since may be sources of dissemination of diarrheogenic E. coli, that can cause from subclinical to severe and fatal infections in children and adults, and also emphasize the need to improve adaptations/adjustments in the manufacturing processes of these products.